Pengaruh Brand Image dan Product Knowledge Terhadap Purchase intention Produk Tas Tiruan Di Kota Denpasar - Wahyuni, Ni Luh Gede; Suparna, Gede (E-Jurnal Manajemen; Vol 3 No 4 (2014), 2014)
This study explains the impact of brand image and product knowledge to purchase intention imitation handbag products in Denpasar. The purpose of the study was to determine the impact of brand image and product knowledge on purchase intention imitation handbag product users in the city of Denpasar. 120 respondents involved in this study that were choosen by purposive sampling technique. The data obtained were then analyzed using multiple linear regression analysis. The results showed that the brand image and product knowledge and a significant positive effect on purchase intention of products imitation bag in Denpasar. It can be concluded that brand image and product knowledge can affect the purchase intention of products imitation bag in Denpasar
Keywords: brand image, product knowledge, purchase intention